Van stichtelijke fraseologie naar redelijkheid. De PvdA en de oorlog in Vietnam, 1964-1973 - Zuijdam, F. (BMGN - Low Countries Historical Review, 2002)
The Dutch Labour Party and the war in VietnamDuring the 1960s, many people demonstrated against the war in Vietnam. However, the Dutch government, along with most of the major political parties in the Netherlands, chose to ignore the vox populi and refused to reject America's policy regarding Vietnam. One exception to that rule was the Dutch Labour Party. From an early stage, the social-democrats had kept a critical watch on American policy and exhibited an increasing resistance to the subsequent military intervention. In adopting this attitude towards the Vietnam War, the Labour Party had to take several developments into account. The reduction in Cold War tensions, the Cultural Revolution and, above all, the shifts in domestic politics all affected the point of view on Vietnam. One very important consideration that should be taken into account was that, at the time, the Labour Party was trapped between new forms of activism and firm opposition, on the one hand, and the wish to join the government on the other. Under these circumstances, a formal letter to the American Ambassador seemed to be the safest vehicle through which Labour's critical attitude towards Vietnam could be expressed.